TUMOR-RELATED CEREBRAL EDEMA: MECHANISMS AND IMAGING FEATURES (Global Conference on Medical and Health Sciences, 2026)
Brain and central nervous system (CNS) malignancies constitute a serious global health concern due to their high mortality rates, significant socioeconomic burden, limited survival outcomes, and profound negative impact on patients’ quality of life. In 2020, approximately 308,102 new cases of brain and CNS tumors were diagnosed worldwide, representing nearly 1.6% of all newly identified cancers. In the same year, an estimated 251,329 deaths were attributed to these tumors, ranking them among the major causes of cancer-related mortality. Although survival rates vary depending on geographic location and access to advanced medical care, the overall prognosis remains unfavorable because many of these tumors are highly aggressive and often detected at advanced stages. Neuroimaging plays a pivotal role in the diagnosis, therapeutic planning, and postoperative monitoring of brain tumors. Computed tomography (CT) remains one of the fundamental imaging modalities in clinical practice. Both contrast-enhanced and non-contrast CT scans are widely used for noninvasive tumor characterization, evaluation of tumor size and location, assessment of mass effect, and pre-treatment planning. CT imaging is also essential in differentiating neoplastic lesions from other intracranial conditions.